Empowering the Kunci Village Tourism Awareness Group (Pokdarwis) to Enhance Geosite Tourism at Goa Macan through the Integration of 3R and MOF Approaches - Muhammad Bakhru Thohir; Meytria Anggita; Octavia Ranja Riskulloh; Nurhidayah; Yono (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
Kunci Village, Dander District, Bojonegoro Regency, possesses significant tourism potential through the Goa Macan geosite; however, its development remains limited due to low community awareness, the absence of a formal management institution, inadequate accessibility, and minimal digital promotion. This community service program aimed to strengthen the capacity of the Village Tourism Awareness Group (Pokdarwis) in managing and promoting the geosite. The program adopted a collaborative approach integrating Susan Walsh’s 3R framework (Rights-Based, Respect-Based, and Resilience-Based) with the Metal Organic Framework (MOF) concept to enhance stakeholder networking and community participation. Activities included institutional strengthening through the establishment of Pokdarwis regulations, socialization programs, capacity-building workshops, and follow-up planning involving local youth and stakeholders. The results demonstrated substantial improvements in community awareness, the establishment of a formal Pokdarwis institution with approved statutes and bylaws, enhanced tourism management capacity, initial improvements in site accessibility, and strengthened digital promotion skills through Canva and CapCut training. The integration of the 3R and MOF approaches effectively promoted community engagement, respect for local values, and access to digital technology. These findings highlight the importance of continuous mentoring, multi-stakeholder collaboration, and integrated marketing strategies to support the sustainable development of village-based geotourism.